Use of an intragastric balloon for management of obesity in a dog. (15th October 2020) - Vedrine, B.; Fernandes, D.; Gérard, F.; Fribourg‐Blanc, L.‐A.
Abstract : While various bariatric surgeries are commonplace in obesity medicine for humans, these techniques have not been commonly used in veterinary medicine. A technique used in humans consists in endoscopically placing an intragastric balloon. The intragastric balloon takes volume in the stomach causing a feeling of satiety and reducing food intake. A 57.6 kg, 9‐year‐old neutered female Labrador dog with chronic hypothyroidism was presented for overweight management. Combined levothyroxine treatment and dietary management with specific alimentation for obesity had failed to control overweight. An intragastric balloon was placed endoscopically in the stomach to allow the reduction of the gastric capacity and resulted in effective weight loss. The dog weight decreased to 40.9 kg at the time of intragastric balloon removal 198 days after placement. Further research including a larger sample size and long term follow‐up is required to establish safety and effectiveness of this procedure.